Contemporary Concepts of Schizophrenia - Kavitha, J.; Sivakrishnan, S. (Issues and Developments in Medicine and Medical Research Vol. 10, 2022)
Schizophrenia (SCZ) a mental illness that impairs one's capacity to think rationally, control emotions, make decisions, and interact with others. It's a chronic medical condition. Schizophrenia can appear at any age, but usually occurs in late teens to early 20s for men and late 20s to early 30s for women. SCZ is infrequent in children under 12 and in persons over 40. It is possible to be happy with schizophrenia. A lack of desire is one of the hallmarks of SCZ. Therapy can significantly alleviate most symptoms of SCZ and reduce the likelihood of relapse. It's not a cure for SCZ, but it's improving treatment options. Experts looks at genetics, behavioural study, and advanced imaging to better understand the brain's structure and function. SCZ treatment includes medication, therapy, lifestyle adjustments, and social support that leads to new and more effective life.